2008
DOI: 10.1021/ma801236p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Elastomeric Polypropylenes Studied with Atomic Force Microscopy

Abstract: The energy dissipated between tip and sample during dynamic atomic force microscopy (AFM) is a sensitive measure of local surface properties. We mapped the surface properties of crystalline and amorphous regions in thin films of different kinds of elastomeric polypropylene (ePP) with 10 nm lateral resolution. The dissipated energy as a function of the amplitude setpoint displays discriminative shapes for both polymer regions. Differences in the shape as well as in the maximum amount of dissipated energy are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 44 publications
(102 reference statements)
4
31
0
Order By: Relevance
“…We attribute the shape of the PB curves to viscoelastic dissipation processes 19 and note the plateau-like shape of the PS curves, similar to those curves observed on crystalline regions of polypropylene. 24 Figure 1 panels f and g show the analysis of the APD curves according to ref 21. Conservative and dissipative contributions to the total tipϪsample interaction force are expressed by an additional tipϪsample spring constant k TS and the effective damping parameter ␣ eff /m.…”
Section: Resultsmentioning
confidence: 99%
“…We attribute the shape of the PB curves to viscoelastic dissipation processes 19 and note the plateau-like shape of the PS curves, similar to those curves observed on crystalline regions of polypropylene. 24 Figure 1 panels f and g show the analysis of the APD curves according to ref 21. Conservative and dissipative contributions to the total tipϪsample interaction force are expressed by an additional tipϪsample spring constant k TS and the effective damping parameter ␣ eff /m.…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48] Furthermore, the APD curves yield the z-axis position of the unperturbed surface as well as the tip indentation. 22,44,[49][50][51] On hydrated collagen fibrils, the tip indentation reaches up to 3.5 nm. 22 Spitzner et al 45 demonstrated how height and phase images can be reconstructed for multiple set points from one data set of APD curves measured within a specified surface area.…”
Section: Introductionmentioning
confidence: 99%
“…However, the next-neighbor distance between two adjacent surface amino groups must be below the AFM tip diameter (≈30 nm) as no distinct height steps or islands could be observed in the AFM images. A resolution of the density of bound molecules may be possible by using novel techniques such as the measurement of AFM amplitude–phase–distance curves [40]. From such experiments, the dissipated energy of the AFM tip oscillation can be calculated, which depends on the local elastic and therefore structural surface properties of the substrate.…”
Section: Resultsmentioning
confidence: 99%